دور التشخيص الاستراتيجي للبيئة الداخلية في ترشيد اتخاذ القرارات في المؤسسة - دراســـة عـينـة مـن المؤسسـات - بلقاسم, حمادي; عبد المنعم, مسيني; كمال, العابد (University of eloued جامعة الوادي, 2020)
"تُركّز هذه الدراسة على تأثير التشخيص الاستراتيجي لعناصر البيئة الداخلية على ترشيد عملية اتخاذ القرارات الإدارية في المؤسسة الاقتصادية، فالبيئة الداخلية التي تتكون منها المؤسسات مختلفة وغير متشابهة، وبالتالي من الضروري على المؤسسة القيام بتشخيص بيئتها الداخلية بصورة متسمرة بغية تحديد نقاط القوة التي تمتلكها ومن ثمة استغلالها وكذا تحديد نقاط الضعف التي تعاني منها ومحاولة تقليلها. وانطلاقا مما سبق قمنا بطرح الإشكالية التالية: ما هو دور التشخيص الاستراتيجي للبيئة الداخلية في ترشيد اتخاذ القرارات الإدارية في المؤسسات الاقتصادية؟ لقد اعتمدنا في دراستنا على المنهج الوصفي في الجانب النظري، أما الجانب التطبيقي فقد اعتمدنا على المنهج التحليلي، وتمثلت أداة الدراسة في الاستبيان الذي تم توزيعه على عينة من 57 فرد من مسيّرين وغير مسيّرين لمؤسسات اقتصادية بولاية الوادي في الفترة الممتدة من شهر جانفي 2020 إلى غاية شهر اوت من نفس السنة. وقد توصلنا من خلال الدراسة المسحية على عينة من المؤسسات بولاية الوادي التي قمنا بها إلى أن التشخيص الاستراتيجي للبيئة الداخلية يؤثر على اتخاذ القرارات الإدارية في المؤسسة من خلال توفير معلومات عن مختلف عناصر البيئة الداخلية في الوقت المناسب التي بدورها تسمح بترشيد القرارات من طرف متخذها. ""This study focuses on the effect of the strategic diagnosis of the elements of the internal environment on rationalizing the process of administrative decision-making in the economic institution. The internal environment that consists of institutions are different and not similar, and therefore it is necessary for the institution to consistently diagnose its internal environment in order to determine the strengths it possesses and then exploit it. As well as identifying the weaknesses that suffer from and trying to reduce them. Based on the above, we have raised the following problem: What is the role of the strategic diagnosis of the internal environment in rationalizing administrative decision-making in economic institutions? We have relied in our study on the descriptive approach in the theoretical side, as for the applied side, we have relied on the analytical approach, and the study tool was represented in the questionnaire that was distributed to a sample of 57 individuals who are managers and non-managers of economic institutions in the state of the Valley in the period from January 2020 until The month of August of the same year. And through the survey study on a sample of institutions in the wilayat of the valley that we did, we found that the strategic diagnosis of the internal environment affects the administrative decision-making in the institution by providing information on the various elements of the internal environment in a timely manner, which in turn allows for rationalization of decisions by the one who makes them. "
مذكرة ماستر اقتصاد مؤسسة
Keywords: تشخيص استراتيجي، بيئة داخلية، اتخاذ القرار.; Strategic diagnosis, Internal environment, Decision-making.